Peran Mediasi dalam Penyelesaian Perceraian Pegawai Pemerintah dengan Perjanjian Kerja Akibat Tekanan Ekonomi: Perspektif Hukum Keluarga Islam: The Role of Mediation in Resolution of Divorce Disputes Between Government Employees with Work Agreements due to Economic Pressure: An Islamic Family Law Perspective - Ghina Nadiah; Musleh Harry (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The phenomenon of increasing divorce rates among Government Employees with Employment Agreements (PPPK) is an issue that requires serious attention, considering the complexity of the economic, social, and psychological factors that underlie it. Uncertainty of employment status, limited income, and high workloads have implications for tension in household relations and decreased family resilience. This study aims to analyze the role of mediation in resolving PPPK divorce cases due to economic pressure from the perspective of Islamic Family Law. The research method used is a literature review by examining various literature sources, laws and regulations, and the results of relevant previous research. The results show that economic pressure is the dominant factor driving the increasing PPPK divorce rate, while mediation functions not only as a dispute resolution mechanism but also as an instrument of family protection through an ishlah approach that emphasizes the values ​​of justice, welfare, and moral responsibility. This study contributes to enriching the study of Islamic Family Law through a contextual analysis of the dynamics of PPPK divorce, which has its own characteristics compared to non-PPPK couples. In addition, this study emphasizes the importance of strengthening mediation based on Islamic values ​​as a preventive measure against family disintegration due to economic pressure.